SCHIZENCEPHALY - mariesta mariesta (Faculty of Medicine Universitas Kristen Duta Wacana, 2017)
BACKGROUND Schizencephaly is a rare case, usually related with brain system development injury with cleft in cortex cerebral. METHODS Case report. Man 30 years old, as a trainner outbond, last bachelor education, came with left ankle fracture. There’s left limb weakness since birth and athropy of left arm. PURPOSE To prevent early limitation of activity daily living and to educate parents. CONCLUSION There’s no all sign and symtoms in the schizencephaly patient, depend on the stages. Physiotherapy for increasing activity daily living. Keywords : Schizencephaly, IQ, trauma, seizure